Rethinking pedagogy for a digital age : - Beetham, Helen (Routledge, 2007)
Incorporating a variety of contexts ? face-to-face, self-directed, blended and distance learning modes ? this book examines different perspectives on effectively designing and delivering learning activities to ensure that future development is pedagogically sound, learner focused and accessible.nbsp;It considers key topics including: specific activities for achieving learning outcomes classifies and clarifies technologies? uses for learning and role in educational design current systems and future developments learners? competencies and approaches designing for mobile technologies practitioner development sustainability, organisational barriers and learning communities. Illustrated by case studies from the disciplines and with a helpful appendix of tools and resources for researchers, practitioners and teachers, this book is an essential guide to effective design and implementation of sound e-learning activities.